2020
DOI: 10.1097/md.0000000000021089
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of alendronate for the treatment of ankylosing spondylitis

Abstract: Background: Ankylosing spondylitis (AS) is a very tricky orthopedic disorder. If such condition cannot be managed fairly well, it may significantly affect quality of life and even leads to disability among such population. A variety of studies have reported that alendronate is utilized for the treatment of AS. However, their results are still contrary, and no systematic review has addressed on this topic. Thus, this study will systematically assess the efficacy and safety of alendronate for the tr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…Eight RCTs (15,(17)(18)(19)(20)(21)(22)(23) utilized BASDAI to assess the improvement of AS, which include 247 patients in IGU group and 225 patients in control group. The heterogeneity test showed that P<0.00001, I2 = 86%, which suggest that the heterogeneity is high, and the random effects model was used for analysis.…”
Section: Basdaimentioning
confidence: 99%
See 2 more Smart Citations
“…Eight RCTs (15,(17)(18)(19)(20)(21)(22)(23) utilized BASDAI to assess the improvement of AS, which include 247 patients in IGU group and 225 patients in control group. The heterogeneity test showed that P<0.00001, I2 = 86%, which suggest that the heterogeneity is high, and the random effects model was used for analysis.…”
Section: Basdaimentioning
confidence: 99%
“…Nine RCTs (15)(16)(17)(18)(19)(20)(21)(22)24) (284 patients in experimental group and 258 patients in control group) reported adverse events. The heterogeneity test P=0.37, I2 = 8%, indicating that the included studies are heterogeneous, and the fix effects model is used for analysis.…”
Section: Adverse Eventsmentioning
confidence: 99%
See 1 more Smart Citation